Analysis of Water and Sediment Quality, Mercury Pollution and Its Effect on Bacterial Populations in the Tabir River, Merangin Regency, Jambi Province - Rismayanti; Khoe Susanto Kusumohadi; Asnelly Ridha Daulay (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
This research was conducted to determine the quality of the Tabir River which is increasingly being damaged by illegal gold mining. The purpose of this study was to determine the water quality and concentration of Hg in the water and sediment of the Tabir river and its correlation to bacterial population. Water and sediment samples were taken from 6 segments along the Tabir river to check pH, Hg, and total bacteria in each segment. Data analysis used the pollutant index method and the correlation was tested with SPSS 22. The results of observations on river water showed that the average pH was normal in the range of 6.6-7.1 and the level of Hg contamination was heavily polluted with a score of 10.72. On the river sediments, pH in segments 1 to 5 was in accordance with the quality standard, which ranged from 6.2 to 7.1 and in segment 6 was below the quality standard 5.9 while the level of Hg contamination ranged from 3-35Mg/L and lightly polluted with a score of 3.4. The number of bacterial populations in the waters ranged from 1.52 x 104 to 9.40 x 103. Correlation analysis showed a significance value of 0.889, that can be concluded that the presence of Hg in the waters of the Tabir river does not have a significant effect on the number of bacterial populations. The number of bacterial populations in the sediment ranged from 3.00 x 104 to 9.05 x 103. Correlation analysis obtained a significance value of 0.254 that can be concluded that the presence of Hg does not have a significant effect on the number of bacterial populations in the sediment of the Tabir river.